INFLUENCE OF SERVICE QUALITY, BRAND IMAGE, AND COMMUNICATION ON PATIENT SATISFACTION AND LOYALTY OF UROLOGY PATIENT AT SILOAM HOSPITAL MANADO IN 2023 - Toreh, Christof; Wuisan, Dewi Sri Surya (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. Indonesia's entry into the free-market competition has led to a surge in the number of hospitals, resulting in intensified competition with increasingly selective consumers, higher expectations, and lower loyalty. According to the 2022 report from Siloam Hospital Manado, there has been a decline in urology patient visits, and no research has been conducted on patient satisfaction levels regarding service quality, brand image, communication, and their impact on urology patient loyalty. This situation raises concerns about a potential decline in patient visits, which is crucial during this period to enhance the hospital's marketing function for achieving patient satisfaction and loyalty. To analyze the influence of service quality, brand image, and communication on patient satisfaction and their subsequent impact on patient loyalty. This study employs a descriptive-analytic design with a quantitative approach, utilizing purposive sampling with a sample size of 161. Data is collected through questionnaires, and the analysis is conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Abstrak. Masuknya Indonesia ke dalam persaingan pasar bebas telah menyebabkan lonjakan jumlah rumah sakit, sehingga persaingan menjadi semakin ketat dengan konsumen yang semakin selektif, ekspektasi yang lebih tinggi, dan loyalitas yang lebih rendah. Berdasarkan laporan RS Siloam Manado tahun 2022, terjadi penurunan kunjungan pasien urologi, dan belum dilakukan penelitian mengenai tingkat kepuasan pasien mengenai kualitas pelayanan, brand image, komunikasi, dan dampaknya terhadap loyalitas pasien urologi. Situasi ini menimbulkan kekhawatiran akan potensi penurunan kunjungan pasien, yang sangat penting pada periode ini untuk meningkatkan fungsi pemasaran rumah sakit guna mencapai kepuasan dan loyalitas pasien. Untuk menganalisis pengaruh kualitas layanan, citra merek, dan komunikasi terhadap kepuasan pasien dan dampak selanjutnya terhadap loyalitas pasien. Penelitian ini menggunakan desain deskriptif-analitik dengan pendekatan kuantitatif, menggunakan purposive sampling dengan jumlah sampel 161. Data dikumpulkan melalui kuesioner, dan analisis dilakukan menggunakan Structural Equation Modeling-Partial Least Squares (SEM-PLS).